BOARD GENDER DIVERSITY AND DIVIDEND POLICY IN INDONESIA: IMPACT OF OWNERSHIP STRUCTURE - Mohamad Nur Utomo; Kaujan Kaujan; Adi Sutrisno; Rahmi Nur Islami (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Gender diversity in the corporate boards can determine dividend policy. The objective of this research is to conduct empirical test over the effect of gender diversity in commissioner and director boards on dividend policy with institutional ownership as moderation variable. Research sample is the companies listed at Indonesia Stock Exchange on period 2018-2022 and paying cash dividend. Data analysis is done using SEM-PLS with computer application of WarpPLS 8.0. The result of research shows that the positive effect of diversity gender in commissioner board on dividend policy is determined by institutional ownership. Gender diversity in director board has positive effect on dividend policy without moderation of institutional ownership. In general, these results are consistent to the agency theory that states that dividend payout can reduce agency problem.